Application of Augmented Reality Technology in Children’s Picture Books Based on Educational Psychology - Wang, Rui (Frontiers in Psychology, 2022)
To cultivate children's imagination, observation, thinking ability, and aesthetic consciousness, the questionnaire survey is adopted to analyze the design strategies and principles of children's picture books based on Augmented Reality (AR). Primarily, the related concepts and theories are expounded for the research content. Children in preschool-aged 4-5 years are invited as primary participants in the present work, and the psychological characteristics of the invited children are analyzed in depth. Then, a study is carried out on the existing AR children’s picture books. The problems existing in the design of AR children’s picture books are found and then related solutions are put forward based on the results of the questionnaire survey. Besides, a design is made on the strategies and interactive design principles of AR children’s picture books on mobile terminals that are more in line with the needs of children. The results show that 41.07% of parents do not understand AR technology, and 37.5% of preschool children indicate that they do not operate mobile devices independently. However, they need the assistance of parents to use this kind of picture book. 44.64% of parents believe that the main problem of AR picture books in the current market is the lack of interesting interaction. Given the above problems, five principles are proposed for the design of AR children’s picture books based on mobile terminals, namely, easy operation principle, interesting principle, guiding principle, timely feedback principle and safety principle. A set of universally applicable design methods are proposed for AR children’s picture books based on mobile terminals, which provides certain theoretical guidance for the development of related types of products.